Evaluation of the explosive force characteristic of arms and legs among the handball players U19 - Sabira, M. B.; Larbi, C.; Ibrahim, F. (Sciences de l`expertise et de la technologie des activités physiques et sportives, 2023)
Our study aimed to evaluate the explosive strength of the lower and upper limbs in young handball players (u 19 years old) during the preparatory period; using the most commonly used field tests in handball (medicine ball throwing; horizontal and vertical jumping), Our descriptive study was practiced on a sample of 147 young handball players taken from a population of 287 of the u 19 handball teams who play in (excellence; national 1.2 western region). From the analysis of the test results, it was deduced that: